Proteomes of Extracellular Vesicles From Pancreatic Cancer Cells and Cancer-Associated Fibroblasts. Issue 7 (August 2022) - Pan, Sharon; Lai, Lisa A.; Simeone, Diane M.; Dawson, David W.; Yan, Yuanqing; Crnogorac-Jurcevic, Tatjana; Chen, Ru; Brentnall, Teresa A.
Abstract : Objectives: Extracellular vesicles (EVs) are lipid bound vesicles secreted by cells into the extracellular environment. Studies have implicated EVs in cell proliferation, epithelial-mesenchymal transition, metastasis, angiogenesis, and mediating the interaction of tumor cells and microenvironment. A systematic characterization of EVs from pancreatic cancer cells and cancer-associated fibroblasts (CAFs) would be valuable for studying the roles of EV proteins in pancreatic tumorigenesis. Methods: Proteomic and functional analyses were applied to characterize the proteomes of EVs released from 5 pancreatic cancer lines, 2 CAF cell lines, and a normal pancreatic epithelial cell line (HPDE). Results: More than 1400 nonredundant proteins were identified in each EV derived from the cell lines. The majority of the proteins identified in the EVs from the cancer cells, CAFs, and HPDE were detected in all 3 groups, highly enriched in the biological processes of vesicle-mediated transport and exocytosis. Protein networks relevant to pancreatic tumorigenesis, including epithelial-mesenchymal transition, complement, and coagulation components, were significantly enriched in the EVs from cancer cells or CAFs. Conclusions: These findings support the roles of EVs as a potential mediator in transmitting epithelial-mesenchymal transition signals and complement response in the tumor microenvironment and possibly contributing to coagulation defects related to cancer development.